0004 Developing a community-based car seat program. (26th April 2015) - Werst, Janet
Abstract : Statement of purpose: Motor vehicle crashes are the leading cause of injury and death to children in the United States. By developing a community-based car seat program, complete with community partners, we can impact the severity of injuries and reduce the death rates. Methods/Approach: By bringing together all stakeholders to discuss motor vehicle crashes, the leading cause of injury and death to children in our community, Safe Kids Larimer County was able to develop a comprehensive, coordinated effort using the Community Guide to Preventative Services recommendations. Our collaborative effort has helped us address our community's health needs and address health disparities. Our approach has also helped foster community relationships, prevent burnout of Child Passenger Safety Technicians, and increase our collective impact. Results: Death rates for children in motor vehicle crashes and injury rates have declined and the number of children properly restrained in car seats has increased since the inception of the program in 2002. Community parternships/relationships have been strengthened. Conclusions: In order to impact injury due to motor vehicle crashes there must be a coordinated and comprehensive approach. Safe Kids Larimer County has demonstrated how to work with all entities for the greater good of keeping our kids safe. Our program has been successful due to the partnerships built and is being replicated throughout the state. Significance and contribution to the field: Safe Kids Larimer County can assist other communities in replicating our success to make an impact on motor vehicle injuries and deaths to children by sharing our resources.